2016
DOI: 10.1093/ijnp/pyw096
|View full text |Cite
|
Sign up to set email alerts
|

Serum Brain-Derived Neurotrophic Factors in Taiwanese Patients with Drug-Naïve First-Episode Major Depressive Disorder: Effects of Antidepressants

Abstract: Background:Brain-derived neurotrophic factors are known to be related to the psychopathology of major depressive disorder. However, studies focusing on drug-naïve first-episode patients are still rare.Methods:Over a 6-year period, we examined the serum brain-derived neurotrophic factors levels in patients with first-episode drug-naïve major depressive disorder and compared them with sex-matched healthy controls. We also investigated the relationships between serum brain-derived neurotrophic factors levels, suic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 31 publications
3
26
2
1
Order By: Relevance
“…Other studies demonstrated that antidepressant treatment increased central BDNF levels in animals ( 12 ) as well as peripheral BDNF levels in humans ( 10 , 20 22 ). However, these finding are inconsistent, at least in humans, as other studies have shown decreases of peripheral BDNF levels during the course of treatment as well ( 23 ), no change at all ( 24 ) or differences between antidepressants ( 25 ). An especially interesting biological marker for therapy response prediction may be BDNF exon IV promoter methylation which has gained high interest in recent years, as it was shown that especially this promoter site controls BDNF expression ( 26 ).…”
Section: Introductionmentioning
confidence: 94%
“…Other studies demonstrated that antidepressant treatment increased central BDNF levels in animals ( 12 ) as well as peripheral BDNF levels in humans ( 10 , 20 22 ). However, these finding are inconsistent, at least in humans, as other studies have shown decreases of peripheral BDNF levels during the course of treatment as well ( 23 ), no change at all ( 24 ) or differences between antidepressants ( 25 ). An especially interesting biological marker for therapy response prediction may be BDNF exon IV promoter methylation which has gained high interest in recent years, as it was shown that especially this promoter site controls BDNF expression ( 26 ).…”
Section: Introductionmentioning
confidence: 94%
“…In contrast, decreased BDNF and its receptor tropomyosin-related kinase B (TrkB) contribute to cognitive decline in aging [ 55 , 56 ]. The levels of serum BDNF in patients with drug-naïve first episode depressive disorder were significantly lower as compared to healthy controls [ 57 ]. Reduced protein and mRNA levels of BDNF were found in the hippocampus of postmortem AD samples and MCI patients, [ 58 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…Postmortem studies reported that BDNF expression is lower in AD patients [ 57 , 101 ]. Infusion of amyloid fibrils significantly increased HDAC2 expression and its occupancy in the promoter region of Bdnf exon IV, resulting in histone H3 deacetylation and the suppression of BDNF expression [ 102 , 103 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depressive mood was accompanied by several physiological changes 10 . In the present study, we focused on the possible changes in cortisol and neurotrophins levels, and this biomarker relation with depression and ostomy 11,12 . This marker relationship in ostomy patients is still poorly described.…”
Section: Introductionmentioning
confidence: 99%